Chronic Lung Disease Following Neonatal Extracorporeal Membrane Oxygenation: A Single-Center Experience - Perez Ortiz, Alba; Glauner, Anna; Dittgen, Felix; Doniga, Thalia; Hetjens, Svetlana; Schaible, Thomas; Rafat, Neysan (Frontiers in Pediatrics, 2022)
Objective: To assess the incidence and severity of chronic lung disease after neonatal extracorporeal oxygenation (ECMO) and to identify factors associated with its development. Methods: A retrospective observational study in a neonatal ECMO centre was conducted. All neonates who received support with ECMO in our institution between January 2019 and October 2021 were included and their pulmonary outcome was investigated. Results: A total of 91 patients (60 with congenital diaphragmatic hernia, 26 with meconium aspiration syndrome and 5 with other diagnoses) were included in this study. Sixty-eight (75%) neonates survived. Fifty two (76%) ECMO survivors developed chronic lung disease (CLD). There was no statistical difference between patients with and without CLD with regard to gender or gestational age. Patients with CLD had lower birth weight, were younger at initiation of ECMO and required longer ECMO runs. Patients with congenital diaphragmatic hernia (CDH) developed CLD more often than infants with other underlying disease (94% vs 60%). Seventeen ECMO survivors (25%) developed severe CLD. Conclusions: The incidence of CLD after neonatal ECMO is substantial. Risk factors for its development include CDH as underlying condition, the necessity of an early initiation of ECMO and the need of ECMO over 7 days.